Technical Mentorship of Village Financial Management in Kahaungu Eti Sub-district, East Sumba Regency: Bimbingan Teknis Pengelolaan Keuangan Desa Di Kecamatan Kahaungu Eti, Kabupaten Sumba Timur - Renggo, Yuniarti Reny; Pakereng , Yulita Mila; Suryani, Siti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This Technical Guidance activity aims to improve the capacity of village administrators in managing village finances in a transparent and accountable manner, using methods such as lectures, group discussions and exercises. The Technical Guidance lasted for 3 days with participants from all village administrators from 9 villages in the Kahaungu Eti sub-district. The results showed an increase in participant understanding of up to 55% based on the post-test results. This Technical Guidance needs to be carried out continuously in order to ensure consistency in financial governance.